Kontribusi Motiivasi Orang Tua dan Fasilitas Belajar Terhadap Gaya Belajar dan Dampaknya pada Hasil Belajar Matematika Siswa Kelas VII SMP Negeri 2 Kartasura - Rakhmawati, Intan Aulia, Prof. Dr. Sutama, M.Pd (2017)
Mathematics learning outcomes is important, because mathematics learning outcomes is the end learning process of students after understanding and mastering knowledge or mathematics sciences. But, in fact mathematics learning outcomes is tending not as expected. Mathematics learning outcomes is tending not as expected because of two factors, internal factor and external factor. Internal factor are factors that exist within the individual who is learning, as learning styles. External factor are factors that are beyond of individual, as parental motivation and learning facilities. This study has three purposes. (1) To examine the simultaneous contribution of parental motivation and learning facilities to the mathematics learning outcomes through learning styles as indirect. (2) To examine the simultaneous contribution of parental motivation and learning facilities to the learning styles. (3) To examine the learning styles to the mathematics learning outcomes. This study uses quantitative method. The population of this study is all of the 7th grade students at SMP Negeri 2 Kartasura in academic year 2016/2017. The sample of this study is 168 students. Technique of sample uses random sampling. Technique of collecting data was conducted by questionnaire and documentation. The questionnaire method used to collecting data of parental motivation, learning facilities, and learning styles. While the documentation method used to collecting data of mathematics learning outcomes. The technique of data analysis uses path analysis. This study has three conclusions. (1) There is no simultaneous contribution of parental motivation and learning facilities to the mathematics learning outcomes in 7th grade students at SMP Negeri 2 Kartasura as indirect through learning styles in signification level 5%., but in signification level of 21,5% has 0.027. (2) There is no simultaneous contribution of parental motivation and learning facilities to the learning styles in signification level 5% but in signification level of 7,4% has 0.031 contributions. (3) There is no contribution of learning styles to the mathematics learning outcomes in 7th grade students at SMP Negeri 2 Kartasura in signification level of 5%, but in signification level of 51,4% has 0.003 contributions.